Injuries related to taekwondo training - short report based on experiences from Primary School No. 31 with sports championship classes in Bydgoszcz (Poland) - Sławomir Wąs; Zygmunt Siedlecki (Kazimierz Wielki University, 2022)
Taekwondo has become a very popular sport in Poland and around the world, and training in this martial art begins with young children. Taekwondo trainings are organized in kindergartens and schools, clubs and master classes are organized in sports schools, and children take part in competitions. Taekwondo, like any martial art, carries a potential risk of injury. According to the literature, lower limb injuries are the most common, as in taekwondo the lower limbs are mainly used. Head and spine injuries as a result of falls are also described. The author emphasizes that despite the injuries described in the literature and the frequency of occurrence defined as about 2.5 - 8%, injuries in the sports school in Bydgoszcz are significantly less frequent. The author also points out that there are also injuries (fractures) of the upper limbs, which are ignored by numerous international publications. Despite this, it should be emphasized that taekwondo is a safe sport discipline. Its prevalence among school children is a favorable phenomenon.